Технологічні особливості вантажопідйомного крокуючого модуля (ВПКМ) та його встановлення при монтажі покриттів - Черненко, К. В. (Ways to Improve Construction Efficiency, 2012)
Proposed new advanced walking module for lifting super heavy long-span surfaces that allows to use new assembly technology.